Dielectric phenomena in solids with emphasis on physical concepts of electronic processes - Kao, Kwan-Chi. (Amsterdam ; Boston : Academic Press, 2004)
In general, a dielectric is considered as a non-conducting or insulating material (such as a ceramic or polymer used to manufacture a microelectronic device). This book describes the laws governing all dielectric phenomena. A unified approach is used in describing each of the dielectric phenomena, with the aim of answering "what?", "how?" and "why" for the occurrence of each phenomenon; Coverage unavailable in other books on ferroelectrics, piezoelectrics, pyroelectrics, electro-optic processes, and electrets; Theoretical analyses are general and broadly applicable; Mathematics is simplified and emphasis is placed on the physical insight of the mechanisms responsible for the phenomena; Truly comprehensive coverage not available in the current literature.
Introduction. Electric Polarization and Relaxation. Optical and Electro-Optic Processes. Ferroelectrics, Piezoelectrics and Pyroelectrics. Electrets. Charge Carrier Injection from Electrical Contacts. Electrical Conduction and Photoconduction. Electrical Aging, Discharge and Breakdown Phenomena.
Includes bibliographical references and index.
Keywords: Dielectrics; Electronic books